In veteran outpatients, antibiotics remain significant risk factor for community-acquired Clostridiodes difficile infection - Ukwen Akpoji; Brigid Wilson; Tayoot Chengsupanimit; Sunah Song; Taissa Bej; Robin Jump; Federico Perez (Cambridge University Press, 2022)
Background: An estimated 30% of antibiotic prescriptions in outpatient settings may be inappropriate. Antibiotic exposure increases an individual's risk of Clostridioides difficile infection (CDI). To assess the prevalence of community-acquired CDI (CA-CDI) among patients without recent hospitalization and to examine the influence of outpatient antibiotic exposure on the risk of acquiring CA-CDI in this population, we examined a 2-year cohort of patients seen in primary care clinics at VA community-based outpatient clinics (CBOCs) associated with a large VA medical center. Methods: All primary care visits and nonvisit antibiotic prescriptions were identified in calendar years 2018-2019 as encounters of interest. Encounters occurring Results: We identified 84,787 patients with visits meeting our criteria. In this cohort, 3,533 patients were prescribed antibiotics at their encounter of whom 5 (0.14%) developed CA-CDI. Among the 81,254 patients who were not prescribed antibiotics, 15 (0.02%) developed CA-CDI, yielding an unadjusted CA-CDI odds ratio of 7.68 (95% CI, 2.50-19.82). p Conclusions: Although CA-CDI episodes were infrequent among VA outpatients with a CBOC visit in 2018-2019, the odds of CA-CDI were 7-fold greater in outpatients with antibiotic exposure than outpatients without antibiotic exposure. Antibiotic stewardship interventions that emphasize adverse events as a result of care provided in the outpatient setting, rather than as events limited to acute-care settings, may mitigate CDI risk.